2001
DOI: 10.1002/1097-0215(20011120)95:6<388::aid-ijc1069>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the 3?untranslated region of theCDKN2A gene is common in sporadic primary melanomas but mutations in theCDKN2B,CDKN2C,CDK4 andp53 genes are rare

Abstract: Ten patients with advanced B-cell lymphoma were treated with a single locoregional injection of CD3CD19 bispecific and costimulating CD28 monospecific antibodies to activate tumor-infiltrating T-lymphocytes. Antibodies were administered at 4 different dose levels (30 g, 270 g, 810 g, 1,600 g of each antibody) either by intratumoral or intralym-phatic injection. Most patients developed responses within different compartments of the immune systems (T cells, NK cells) subsequent to the antibody application. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 32 publications
6
74
2
Order By: Relevance
“…This polymorphism has previously been reported to be present in 11% of CEPH parents (Ueki et al, 1994), and found to be associated with familial melanoma risk in Queensland (Aitken et al, 1999), but not with sporadic melanomas (Kumar et al, 2001). The C/T polymorphism at nucleotide 540 in the 3 0 UTR was detected in 14 patients (allelic frequency 8.4%), at a frequency lower than the one previously found in sporadic melanoma (14%) (Kumar et al, 2001).…”
Section: Mutational Analysis Of Ink4a-arf and Cdk4 Genesmentioning
confidence: 53%
“…This polymorphism has previously been reported to be present in 11% of CEPH parents (Ueki et al, 1994), and found to be associated with familial melanoma risk in Queensland (Aitken et al, 1999), but not with sporadic melanomas (Kumar et al, 2001). The C/T polymorphism at nucleotide 540 in the 3 0 UTR was detected in 14 patients (allelic frequency 8.4%), at a frequency lower than the one previously found in sporadic melanoma (14%) (Kumar et al, 2001).…”
Section: Mutational Analysis Of Ink4a-arf and Cdk4 Genesmentioning
confidence: 53%
“…These findings provided the smoking gun fingering this protein as a bona fide melanoma suppressor (for review, see Chin 2003). In addition to the 25%-40% of melanoma-prone families and 0.2%-2% of sporadic melanoma patients harboring INK4A mutations in the coding region (Aitken et al 1999;Tsao et al 2000), polymorphism in both 5Ј and 3Ј untranslated regions (UTRs) that alter translation or possibly regulate message stability of INK4A as well as promoter and splicing mutations of INK4A have since been identified in association with 9p21-linked melanomaprone families (Liu et al 1999;Kumar et al 2001; for review, see Sharpless 2004). In line with this, mice with specific Ink4a inactivation did show increased susceptibility to carcinogen-induced and spontaneous melanoma (Krimpenfort et al 2001;Sharpless et al 2001); however, the phenotype observed was relatively weak.…”
Section: Ink4a-cdk4/6-rb Pathwaymentioning
confidence: 99%
“…Mutations and polymorphisms in the CDKN2A and BRAF genes were detected using single-strand conformation polymorphism and direct DNA sequencing methods as described previously. 23 Homozygous deletions at the CDKN2A locus were detected by real-time PCR method using ABI PRISM 7700 sequence detection system (Applied Biosystems, Foster City, CA). CDKN2A fragment (target) and GAPDH fragment (reference) were co-amplified and measured in real-time mode.…”
Section: Patient Samplementioning
confidence: 99%